Sisters in the faith : Shaker women and equality of the sexes - Wergland, Glendyne R. (University of Massachusetts Press, 2011)
In 1788, following the death of charismatic founder Mother Ann Lee, the celibate religious group known as the Shakers set out to institutionalize equality of the sexes in their theology, government, and daily practice. In this book, Glendyne Wergland evaluates how well they succeeded in that mission.